Core-Shell Nanocapsules Stabilized by Single-Component Polymer and Nanoparticles for Magneto-Chemotherapy/Hyperthermia with Multiple Drugs - Hu, Shang-Hsiu; Liao, Bang-Jie; Chiang, Chin-Sheng; Chen, Po-Jung; Chen, I-Wei; Chen, San-Yuan (Advanced materials (Weinheim), 2012)
Iron‐oxide‐containing double emulsion capsules carrying both hydrophilic and hydrophobic therapeutic molecules can deliver drugs and energy on demand in vivo. Magneto‐chemotherapy/hyperthermia involves a burst‐like release of hydrophilic doxorubicin and hydrophobic paclitaxel, remotely triggered by a high frequency magnetic field, which also releases energy via internalized iron oxide nanoparticles, all contributing to cell kill.